The Vitamin E Derivative Gamma Tocotrienol Promotes Anti-Tumor Effects in Acute Myeloid Leukemia Cell Lines - Paola Ghanem (Nutrients, 2019)
Acute myeloid leukemia (AML) is a blood cancer characterized by the formation of faulty defective myelogenous cells with morphological heterogeneity and cytogenic aberrations leading to a loss of their function. In an attempt to find an effective and safe AML treatment, vitamin E derivatives, including tocopherols were considered as potential anti-tumor compounds. Recently, other isoforms of vitamin E, namely tocotrienols have been proposed as potential potent anti-cancerous agents, displaying promising therapeutic effects in different cancer types. In this study we evaluated the anti-cancerous effects of γ-tocotrienol, on AML cell lines in vitro. For this purpose, AML cell lines incubated with γ-tocotrienol were examined for their viability, cell cycle status, apoptotic cell death, DNA fragmentation, production of reactive oxygen species and expression of proapoptotic proteins. Our results showed that γ-tocotrienol exhibits time and dose-dependent anti-proliferative, pro-apoptotic and antioxidant effects on U937 and KG-1 cell lines, through the upregulation of proteins involved in the intrinsic apoptotic pathway.